DISTRIBUTED GENERATION AND ITS IMPACTS ON POWER SYSTEM - Kapse, Sunildatt Dewaram; Yadav , K. P.; Mustafa , Md. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Todays power requirement are increasing in an irregular pattern and with the increase in the population is performing a very important role in increased power requirement. Also the excessive industrialization leads to the development of new technologies with increased power demand. To handle the power requirements engineers have developed or is developing a new technology which is distributed generation (DG). Nowadays distributed generation is being used widely to deliver the power to the end users as well as add to the power generation capability of any power plant. This paper shows the impacts that were raised due to the connection of distributed generation into the existing network. To test the effectiveness of proposed method an IEEE 30 bus network is used. The impacts are studied and are shown with the help of graph.